Biopatent Law: European vs. US Patent Law - Storz, Ulrich; Quodbach, Martin; Marty, Scott D.; Constantine, Derek E.; Parker, Matthew; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
SpringerBriefs in Biotech Patents presents timely reports on intellectual properties (IP) issues and patent aspects in the field of biotechnology. This volume focus on particular aspects of the US patent law, which can have tremendous differences compared to the European law. This includes questions of biopatent prosecution, novelty, inventive step, written disclosure and sufficiency of enablement as well as questions of law enforcement of biotech patents.
Preface -- Ulrich Storz: Patentability Requirements of Biotech Patents -- Martin Quodbach: Law Enforcement of Biotech Patents -- Scott D. Marty, Derek E. Constantine and Matthew Parker: Particular: Aspects of US Patent Law in Biotechnologies -- About the Authors.
Keywords: Medicine; Biochemistry; Biomedicine; Molecular Medicine; International IT and Media Law, Intellectual Property Law; Biochemistry, general